Designing tuned mass dampers via static output feedback a numerical approach. - Schmitendorf, W.E (Earthquake engineering & structural dynamics.)
The paper presents a numerical approach to the problem of determining the design parameters of a vibration absorber to minimize the effect of disturbing forces. The approach is also applicable to multi-input systems such as civil engineering structures. The resulting devices are appealing since they can be implemented passively and are more economic and reliable than active control devices.